Antibiotics suppress colon tumorigenesis through inhibition of aberrant DNA methylation in an azoxymethane and dextran sulfate sodium colitis model. Issue 1 (13th December 2018) - Hattori, Naoko; Niwa, Tohru; Ishida, Tatsuya; Kobayashi, Kyosuke; Imai, Toshio; Mori, Akiko; Kimura, Kana; Mori, Takeshi; Asami, Yukio; Ushijima, Toshikazu
Abstract : Chronic inflammation is involved in the development of colon cancer by inducing mutations and aberrant DNA methylation in colon epithelial cells. Furthermore, there is growing evidence that colonic microbiota modulates the inflammation response in the host and influences colon tumorigenesis. However, the influence of colonic microbiota on aberrant DNA methylation remains unknown. Here, we show the effect of colonic microbes on DNA methylation and tumorigenicity using a mouse model of human ulcerative colitis. Mice treated with azoxymethane (AOM) and dextran sulfate sodium (DSS) showed an increase in degree of colitis, as estimated by body weight, occult blood, and stool consistency/diarrhea at 2 weeks after treatment, but treatment with antibiotics markedly reduced the severity of the colitis. Although mucosal hyperplasia and increased inflammation‐related genes were observed in the colonic epithelial cells of the AOM/DSS‐treated mice, treatment with antibiotics abrogated these changes. In addition, treatment with antibiotics significantly decreased the number of mucosal nodules from 5.9 ± 5.3 to 0.2 ± 0.6 ( P  <   .01) and area of occupancy from 50.1 ± 57.4 to 0.5 ± 1.4 mm 2 ( P  <   .01). Aberrant DNA methylation of three marker CpG islands ( Cbln4, Fosb, and Msx1 ) was induced by AOM/DSS treatment in colonic mucosae, but this increase was suppressed by 50%‐92% ( P  <   .05) with antibiotic treatment. Microbiome analysis showed that this change was associated with a decrease of the Clostridium leptum subgroup. These data indicate that antibiotics suppressed tumorigenesis through inhibition of aberrant DNA methylation induced by chronic inflammation. Abstract : In the mice treated with antibiotics, the increase in DNA methylation levels in colonic epithelial cells was suppressed. These results showed that treatment with antibiotics suppressed the induction of aberrant DNA methylation. PMR, percentage of methylation reference.